Functional Role of Essential Oils as Antimicrobial and Antioxidat Agents in Food Industry: A Review - Al-Refaie , Doaa; Mehyar , Ghadeer F.; Shahein, Mohammad (Jordan Journal of Agricultural Sciences, 2023)
Essential oils (EOs) possess both antimicrobial and antioxidant activities in food systems. Variations in EOs effectiveness were dictated by their components, effective concentrations, intrinsic factors of food composition as well as extrinsic factors such as storage temperature. The antimicrobial and antioxidant activities of EOs are a result of the presence of phenolic components at high concentrations. EOs could have better effectiveness than single component because these constitutes could act additively or even synergistically in EOs. EOs have antimicrobial activity against wide range of microorganisms and their mode of action is related to disintegration of cellular membrane integrity followed by inactivation of other microbial cells components. The antioxidant mode of action for EOs is related to neutralization free radicals and peroxide decomposition in particularly when tested in meat, dairy, fruits and vegetables. The high effectiveness of EOs indicates that they could replace the synthetic food additives. This scientific review summarizes the most recent studies about effectiveness of EOs as antimicrobial and antioxidant agents to be used in food industry.